Kontrol Negara Tuan Rumah Dalam Sektor Pertambangan Sebagai Instrumen Penegakan Kedaulatan Hukum dan Perlindungan Sumber Daya Alam di Indonesia - Putri, Keisyha Amanda (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Foreign investment in the mining sector places Indonesia in a dilemma between the pragmatic need to attract capital for the sake of economic growth and the constitutional obligation as a welfare law state to protect natural resources for the greater prosperity of the people. This study analyzes how Indonesia uses various instruments of host state control to enforce its legal sovereignty in the mining sector. Using a juridical-normative legal research method, this study examines the investment regulatory framework in Indonesia, ranging from the Capital Planting Act to sectoral regulations in the mining field, in the perspective of legal politics and international investment law. The study results show that although Indonesia has adopted various control instruments such as investment screening, divestment requirements, and environmental obligations their implementation often faces challenges due to pragmatic political configurations and pressures from the international investment legal regime. There exists a constant tension between efforts to provide legal certainty for investors and enforcement of state sovereignty to protect national interests. This study concludes that the effectiveness of host state controls depends heavily on legal political coherence and institutional capacity to balance between economic benefits, social justice, and environmental sustainability.